Recommendations for In Vitro and In Vivo Testing of Magnetic Nanoparticle Hyperthermia Combined with Radiation Therapy. - Gobbo, Oliviero; Spirou, Spiridon V.; Costa Lima, Sofia A.; Bouziotis, Penelope; Vranješ-Djurić, Sanja; Efthimiadou, Eleni; Laurenzana, Anna; Barbosa, Ana Isabel; Garcia-Alonso, Ignacio; Jones, Carlton; Jankovic, Drina (My University, 2018)
Magnetic nanoparticle (MNP)-mediated hyperthermia (MH) coupled with radiation therapy (RT) is a novel approach that has the potential to overcome various practical difficulties encountered in cancer treatment. In this work, we present recommendations for the in vitro and in vivo testing and application of the two treatment techniques. These recommendations were developed by the members of Working Group 3 of COST Action TD 1402: Multifunctional Nanoparticles for Magnetic Hyperthermia and Indirect Radiation Therapy (“Radiomag”). The purpose of the recommendations is not to provide definitive answers and directions but, rather, to outline those tests and considerations that a researcher must address in order to perform in vitro and in vivo studies. The recommendations are divided into 5 parts: (a) in vitro evaluation of MNPs; (b) in vitro evaluation of MNP-cell interactions; (c) in vivo evaluation of the MNPs; (d) MH combined with RT; and (e) pharmacokinetic studies of MNPs. Synthesis and characterization of the MNPs, as well as RT protocols, are beyond the scope of this work.
PUBLISHED
Keywords: Animal models; Biodistribution; In vitro assays; In vivo evalutation; Magnetic nanoparticles; Pharmacokinetics; Cancer; Nanoscience & Materials; NanoMedicine; Translational Nanomedicine; Health